Perkembangan Pasar Kopi Dunia dan Implikasinya bagi Indonesia - Reni Kustiari (Forum penelitian Agro Ekonomi, 2007)
EnglishThe fast growing trend of world coffee production in the world creates an excess of its supply, encouraging a more intense of competition among the exporting countries.  This situation leads to a decreasing trend of fluctuate price of world coffee. The objective of this paper is to assess the world coffee market behavior in order to make an appropriate strategy and direction of coffee industry policies. Indonesia’s market share in traditional market tends to decrease, and therefore, it is necessary to diversify market destination and commodity composition, in addition to efforts to increase the export of processed coffee.IndonesianPesatnya perkembangan produksi kopi dunia telah menyebabkan terjadinya kelebihan pasokan kopi dunia sehingga mengakibatkan persaingan antar negara produsen menjadi semakin ketat dan pada akhirnya harga cenderung tertekan. Tulisan ini bertujuan mengkaji perkembangan pasar kopi dunia agar dapat menjadi pertimbangan dalam menyusun strategi dan arah kebijakan komoditas kopi Indonesia. Pangsa pasar kopi Indonesia di pasar-pasar tradisional cenderung menurun, oleh karena itu diperlukan upaya-upaya antara lain mendiversifikasi pasar tujuan dan produk kopi serta meningkatkan ekspor kopi olahan.